Characteristics of intestinal microbiota in C57BL/6 mice with non-alcoholic fatty liver induced by high-fat diet - Yan, Guangwen; Li, Shuaibing; Wen, Yuhang; Luo, Yadan; Huang, Jingrong; Chen, Baoting; Lv, Shuya; Chen, Lang; He, Lvqin; He, Manli; Yang, Qian; Yu, Zehui; et al. (Frontiers in Microbiology, 2022)
As a representation of the gut microbiota, fecal and cecal samples are most often used in human and animal studies, including in non-alcoholic fatty liver disease (NAFLD) research. However, due to the regional structure and function of intestinal microbiota, whether it is representative to use cecal or fecal contents to study intestinal microbiota in the study of NAFLD remains to be shown. The NAFLD mouse model was established by high-fat diet induction, and the contents of the jejunum, ileum, cecum, and colon were collected for 16S rDNA analysis. Colonic contents (formed fecal balls) were used instead of feces due to the uncertainty of fecal sample collection and the high similarity of fecal and colonic contents microbiota in mice. Compared with normal mice, the diversity and the relative abundance of major microbiota and functional genes of the ileum, cecum and colon were significantly changed, but not in the jejunum. The variation characteristics of microbiota in the cecum and colon (feces) were similar. However, the variation characteristics of intestinal microbiota in the ileum and large intestine segments (cecum and colon) were quite different. Therefore, the study results of cecal and colonic (fecal) microbiota cannot completely represent the results of jejunal and ileal microbiota.